Effects of equation of state on hydrodynamic expansion, spectra, flow harmonics and two-pion interferometry - Dudek, Danuce M.; Qian, Wei-Liang [UNESP]; Wu, Chen; Socolowski, Otavio; Padula, Sandra S. [UNESP]; Krein, Gastao [UNESP]; Hama, Yogiro; Kodama, Takeshi (World Scientific Publ Co Pte Ltd, 2018)
We perform an extensive study of the role played by the equation of state (EoS) in the hydrodynamic evolution of the matter produced in relativistic heavy ion collisions. By using the same initial conditions and freeze-out scenario, the effects of different equations of state are compared by calculating their respective hydrodynamical evolution, particle spectra, harmonic flow coefficients v(2), v(3) and v(4) and two-pion interferometry radius parameters. The equations of state investigated contain distinct features, such as the nature of the phase transition, as well as strangeness and baryon density contents, which are expected to lead to different hydrodynamic responses. The results of our calculations are compared to the data recorded at two RHIC energies, 130 GeV and 200 GeV. The three equations of state used in the calculations are found to describe the data reasonably well. Differences can be observed among the studied observables, but they are quite small. In particular, the collective flow parameters are found not to be sensitive to the choice of the EOS, whose implications are discussed.
Keywords: Hydrodynamic models; collective flow; equation of state; two-pion interferometry